L5 vertebrectomy for the surgical treatment of tumoral and traumatic lesions of L5 vertebra - Kaner, Tuncay (PAGEPress Publications, 2012)
We retrospectively reviewed the clinical characteristics and the surgical results of seven patients treated with L5 vertebrectomy. The pathologies, clinical characteristics, preoperative and postoperative radiological findings, surgical techniques, and instrumentation for seven patients operated on between 1998 and 2009 are presented in this article. Biopsies were performed on all patients except those involving trauma. Patients were followed up at three-month intervals in the first year, at 6-month intervals in the second year, and on a regular basis afterward. One patient had a traumatic L5 burst fracture; the other six had tumoral pathologies in the L5 vertebrae. One tumoral lesion was a chordoma, another was a hemangioma, and the remaining four were metastatic lesions. Radiotherapy and chemotherapy were performed for the metastatic tumor patients during the postoperative period. Patients with renal cancer and chordoma survived for 3 years; patients with lung cancer and bladder cancer survived for 1 year; and patients with breast cancer survived for 16 months. The lumbosacral region presents significant stabilization problems because of the presence of sacral slope. In our opinion, if the lesion involves only the L5 vertebra, anterior cage-filled bone cement or bone graft should be performed, as dictated by the pathology and posterior transpedicular instrumentation. If the lesion involves the L4 vertebra or the sacrum and the L5 vertebra, the instrumentation can be extended to cover other segments with sacral attachments. The present cases involved only L5 vertebra and treatment with short-segment stabilization covering the anterior and posterior columns.